Przydatność koncepcji praktyk repartycji do analizy polskiej kampanii parlamentarnej 2023 roku - Piotr Borowiec (Politeja)
THE USEFULNESS OF THE CONCEPT OF REPARTITION PRACTICES FOR THE ANALYSIS OF THE POLISH PARLIAMENTARY CAMPAIGN IN 2023